2009
DOI: 10.1136/tc.2009.029850
|View full text |Cite
|
Sign up to set email alerts
|

Support for smoke-free policies among smokers and non-smokers in six cities in China: ITC China Survey

Abstract: ObjectiveTo examine levels of support for comprehensive smoke-free policies in six large Chinese cities.MethodsData from Wave 1 of the International Tobacco Control (ITC) China Survey (April–August 2006) were analysed. The ITC China Survey employed a multistage sampling design in Beijing, Shenyang, Shanghai, Changsha, Guangzhou and Yinchuan (none of which has comprehensive smoke-free policies in place). Face-to-face interviews were conducted with 4815 smokers and 1270 non-smokers. Multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
37
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 8 publications
10
37
3
Order By: Relevance
“…This finding is in line with a previous study, regarding factors related to having an in-home smoking ban in Europe, that found women were more likely to be supportive than men 29 . Also, in line with previous studies from other countries 13,22,30,31 , this study showed that supporting the ban was more likely with older age (>65 years of age), believing SHS causes lung cancer, and having increased knowledge on harm caused by smoking. Although previous studies had differing national policies, populations, and varying contextual situations, results of this study show that factors related to support of the smoking bans are similar in the Greek context as well.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in line with a previous study, regarding factors related to having an in-home smoking ban in Europe, that found women were more likely to be supportive than men 29 . Also, in line with previous studies from other countries 13,22,30,31 , this study showed that supporting the ban was more likely with older age (>65 years of age), believing SHS causes lung cancer, and having increased knowledge on harm caused by smoking. Although previous studies had differing national policies, populations, and varying contextual situations, results of this study show that factors related to support of the smoking bans are similar in the Greek context as well.…”
supporting
confidence: 90%
“…Increased public awareness may also prompt non-smokers to advocate for enforcement of the law. Building on beliefs that SHS causes harm leads to compliance with smoke-free legislation even when norms surrounding social acceptability of smoking are not addressed 20,30 . The multivariate analysis showed that smoking specific indicators, dependency and intention to quit, were not significantly related to supporting the ban in bars.…”
mentioning
confidence: 99%
“…The results showed that, overall, there were significant improvements in smoke-free policy implementation, with the vast majority (>90%) of the visited venues prohibiting smoking in indoor areas after the smoke-free law was passed in 2010. This is in line with research showing that once hospitality venues become smoke-free, staff and clients gradually adjust to this change and support the smoke-free policy Li et al 2010). However, smokers and employers/owners were less supportive as compared to non-smokers and employees toward the smoke-free policy in hospitality venues.…”
Section: Discussionsupporting
confidence: 57%
“…showing that once hospitality venues become smoke-free, staff and clients gradually adjust to this change and support the smoke-free policy Li et al 2010). However, smokers and employers/owners were less supportive as compared to non-smokers and employees toward the smoke-free policy in hospitality venues.…”
Section: Discussionmentioning
confidence: 99%
“…In China, for example, the world's largest producer and consumer of tobacco, a recent survey found that about one in two Chinese urban smokers and four in five non-smokers believed that TSE causes lung cancer. The majority (smokers and non-smokers) support comprehensive smoke-free policies in hospitals, schools and public transport vehicles, while support for smoke-free workplaces, restaurants and bars is somewhat lower [47].…”
Section: Protect People From Tobacco Smokementioning
confidence: 99%